2023
DOI: 10.3389/fphar.2023.1199031
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal adverse events induced by immune checkpoint inhibitors: a large-scale pharmacovigilance study

Hao Liu,
Yumin Li,
Jie Li
et al.

Abstract: Background: The musculoskeletal toxicity of immune checkpoint inhibitors (ICIs) is receiving increasing attention with clinical experience. Nevertheless, the absence of a systematic investigation into the musculoskeletal toxicity profile of ICIs currently results in the under-recognition of associated adverse events. Further and more comprehensive investigations are warranted to delineate the musculoskeletal toxicity profile of ICIs and characterize these adverse events.Material and methods: The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Compared with other drugs, atezolizumab, nivolumab, and pembrolizumab were all associated with RORs greater than 1 for osteoporotic fractures, and falls were the most frequently reported comorbidity among all fractures. 7 The authors concluded that their findings contribute to the hypothesis that ICIs may increase the risk of fractures by inducing osteoporosis and falls.…”
mentioning
confidence: 94%
“…Compared with other drugs, atezolizumab, nivolumab, and pembrolizumab were all associated with RORs greater than 1 for osteoporotic fractures, and falls were the most frequently reported comorbidity among all fractures. 7 The authors concluded that their findings contribute to the hypothesis that ICIs may increase the risk of fractures by inducing osteoporosis and falls.…”
mentioning
confidence: 94%